Menentukan Bentuk Kuadrat Bagian Kerucut Dan Permukaan Kuadratik dengan Menggunakan Matriks - Arwan Mhd Said (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
In determining  quadratic forms by using the matrix, the way is to eliminate the tribe the product of  a quadratic form, ie with how to change variables, and will use the results to assess  the graph Conic sections (slices or cross-section of the cone, or conic section ).Problems in this study is how to determine the quadratic forms of conic sections and quadratic surfaces with using Matrix. From these results, it can be concluded that determine the shape of squares of conic sections and quadratic surfaces can be determined by using a matrix